ИЧКИ ИШЛАР ОРГАНЛАРИ ХОДИМЛАРИ ТОМОНИДАН ЎҚОТАР ҚУРОЛЛАРНИ ҚЎЛЛАНИЛИШИ ЮЗАСИДАН МУСТАҚИЛ ДАВЛАТЛАР ҲАМДЎСТЛИГИ ВА ХОРИЖИЙ ДАВЛАТЛАР ТАЖРИБАСИ - Алижонов, А.Т. (SCIENCE and SOCIETY, 2025)
This scientific article provides a comparative legal analysis of the practice and experience of using firearms by employees of internal affairs bodies (police) of foreign countries and countries of the Commonwealth of Independent States. The legislation of the USA, Ukraine, Georgia, the Czech Republic, Slovenia, the Russian Federation, Armenia, Lithuania, Latvia, the Kyrgyz Republic, Azerbaijan, the Republic of Belarus, Kazakhstan and Tajikistan is compared with our national legislation.